2014
DOI: 10.1002/dta.1669
|View full text |Cite
|
Sign up to set email alerts
|

Studies on drug metabolism by fungi colonizing decomposing human cadavers. Part II: biotransformation of five model drugs by fungi isolated from post‐mortem material

Abstract: The present study investigated the in vitro metabolic capacity of 28 fungal strains isolated from post-mortem material towards five model drugs: amitriptyline, metoprolol, mirtazapine, promethazine, and zolpidem. Each fungal strain was incubated at 25 °C for up to 120 h with each of the five models drugs. Cunninghamella elegans was used as positive control. Aliquots of the incubation mixture were centrifuged and 50 μL of the supernatants were diluted and directly analyzed by liquid chromatography-tandem mass s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…For a further evaluation of the structure of the molecule, the seized drug was submitted also to NMR analysis. The assignation of 1 H and 13 C chemical shifts, expressed in ppm relative to TMS, are reported in Table 1 However, both 1 H and 13 C NMR spectra resulted essentially identical with those reported for 2-amino-1-(4-Br-2,5-dimethoxyphenyl)ethan-1-one by the European Monitoring Center for Drugs and Drugs Abuse (internal unpublished data) and successively by Power et al [18] The present analytical approach, based on the combination of the information obtained employing different analytical techniques, already adopted for the identification of unknown seized samples, [27] allowed the identification of bk-2-CB in the seized material. bk-2-CB, to our knowledge, is not at the moment an explicitly controlled substance in any country, although in Italy it can be considered an analogue of cathinones and therefore scheduled.…”
Section: Nmr Analysissupporting
confidence: 65%
See 2 more Smart Citations
“…For a further evaluation of the structure of the molecule, the seized drug was submitted also to NMR analysis. The assignation of 1 H and 13 C chemical shifts, expressed in ppm relative to TMS, are reported in Table 1 However, both 1 H and 13 C NMR spectra resulted essentially identical with those reported for 2-amino-1-(4-Br-2,5-dimethoxyphenyl)ethan-1-one by the European Monitoring Center for Drugs and Drugs Abuse (internal unpublished data) and successively by Power et al [18] The present analytical approach, based on the combination of the information obtained employing different analytical techniques, already adopted for the identification of unknown seized samples, [27] allowed the identification of bk-2-CB in the seized material. bk-2-CB, to our knowledge, is not at the moment an explicitly controlled substance in any country, although in Italy it can be considered an analogue of cathinones and therefore scheduled.…”
Section: Nmr Analysissupporting
confidence: 65%
“…The resulting molecule is quite instable when analyzed by GC/MS. Due to a probable thermal degradation, as reported by Power et al, [18] the signal for the peak related to bk-2C-B is quite low, and several additional peaks are detectable, all showing in their spectra the 243/245 base peak ions (Br-containing acylium ions). A much better chromatographic behaviour, as well as better structural information, were obtained after derivatization with 2,2,2-trichloroethyl chloroformate.…”
Section: Gc/ms Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…Until recently, very little was known about the metabolic potential of such fungi with respect to xenobiotics relevant to postmortem toxicology, although fungi are eukaryotes sharing more similarities with mammalian cells than prokaryotic bacteria and are known to express metabolic enzymes such as CYP enzymes and peroxidases. Incubation experiments performed by Martinez-Ramirez et al with five model drugs (amitriptyline, metoprolol, mirtazapine, promethazine, and zolpidem) and 28 fungal strains isolated from decomposing bodies recently showed that all these strains were capable of drug metabolism (Martinez-Ramirez, Walther, & Peters, 2015), although their metabolic potential differed considerably. For example, strains from the genus Candida generally showed little metabolic activity forming few metabolites and in small amounts, whereas a strain of the species Bjerkandera adusta metabolized a considerable percentage of the added model drugs forming multiple metabolites: amitriptyline (14% parent drug remaining after 5 days of incubation, 20 metabolites formed), metoprolol (72%, 3), mirtazapine (0%,7), promethazine (0%, 3), and zolpidem (76%, 5).…”
Section: Influences By Postmortem Fungal Metabolism Of Xenobioticsmentioning
confidence: 99%
“…However, some of the formed metabolites were fungispecific and could potentially be useful indicators of postmortem fungal metabolism. Indeed, a fungi-specific hydroxy metabolite of zolpidem was detected in two postmortem blood samples positive for zolpidem from which fungi capable of forming this particular metabolite had been isolated (Mucor circinelloides and Aspergillus jensenii) whereas it could not be detected in postmortem blood from four other cases from which no such fungi could be isolated (Martinez-Ramirez et al, 2015). Altogether, these findings suggest postmortem fungal metabolism may influence concentrations and metabolic patterns of xenobiotics in postmortem samples, but is unclear at this time whether the extent of this influence could reach the same level as described for postmortem bacterial metabolism.…”
Section: Influences By Postmortem Fungal Metabolism Of Xenobioticsmentioning
confidence: 99%